KARY A AL TERNATIF MAHASISWA (KAM) PENGEMBANGAN KEWIRAUSAHAAN PERCETAKAN SABLON MAHASISW A JURUSAN PLB FIP UNIVERSITAS NEGERI YOGYAKARTA - -, Haryanto (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2003)
This  program  is  aimed  at  givmg   the  students  knowledge  and  practical  skills through  screen  printing   training   in   skill   education  subject   in   special  education department.   The objectives 6:f'the"program  are (1)  The students know about screen printing knowledge and theotY,'«~) -Have screen printing practical  skills from setting, making klise, copying up to printing on the paper, plastic fabric, and solid matter, (3) Master in management and marketing, and (4) able to arrange a proposal for printing entrepreneurship.The methods  of this program are: (l)   Speech, giving information about screen printing knowledge and prospect, future chance, (2) Demonstrating the steps of screen printing from setting up to making the product, (3) Giving task, the students apply the screen printing knowledge they  have  from  setting up to  the  printing  on the  various printing product, and (4) Discussion, discussing about the students difficulties in screen printing.The products outcomes of this program are: (1) Paper yields cards, calendars, small boxes, invitations cards, stickers, (2) Cloth yields T-shirt, flag, banners, headbands, and syals, (3) Plastic yields, stickers, plastic bags, stopmaps, labels, and (4) Solid matters yield souvenir, name plate, souvenir (the hung key). .Key words:    entrepreneurship,   and  screen  printing  training.